Fine particle concentrations and exposure in different indoor and outdoor microenvironments during physical exercising - Klara Slezakova (2019)
Although regular exercise improves overall well-being, increased physical activity results in enhanced breathing which consequently leads to elevated exposure to a variety of air pollutants producing adverse effects. It is well-known that one of these ambient air contaminants is ultrafine particles (UFP). Thus, this study aimed to (1) examine exposure to particle number concentrations (PNC) in size ranging from N20-1000 nm in different sport environments and (2) estimate the respective inhalation doses across varying activity scenarios based upon the World Health Organization recommendations for physical activity. PNC were continuously monitored (TSI P-Trak (TM) condensation particle counter) outdoors (Out1-Out2) and indoors (Ind1-Ind2; fitness clubs) over 4 weeks. Outdoor PNC (total median 12 563 # cm(-3); means of 20 367 # cm(-3) at Out1 and 7 122 # cm(-3) at Out2) were approximately 1.6-fold higher than indoors (total median 7 653 # cm(-3); means of 11 861 # cm(-3) at Ind1 and 14 200 # cm(-3) at Ind2). The lowest doses were inhaled during holistic group classes (7.91 x 10(7)-1.87 x 10(8) # per kg body weight) whereas exercising with mixed cardio and strength training led to approximately 1.8-fold higher levels. In order to optimize the health benefit of exercises, environmental characteristics of the locations at which physical activities are conducted need to be considered.